Morphological Studies on the Gills of Puffer Fish (Lagocephalus sceleratus, Gmelin, 1789) - Abumandour,Mohamed M. A (Sociedad Chilena de Anatomía, 2016)
In the present study, we focused on the morphology of L. sceleratus gills using gross anatomy, scanning electron microscopy as well as light microscopy. Results of this study revealed that the gill openings appeared as simple slits anterior to the pectoral fin without distinct opercular cover. The gill system consisted of three pairs of gill arches carrying two rows of gill rakers on its concave border and gill filaments on its convex border. SEM showed that all surfaces of the gill arch were characterized by the presence of the longitudinal ridges with many taste buds in addition to many spines around the rakers. Histologically, the gill arch was composed of curved bar of hyaline cartilage with slightly elevated area corresponding to the sites of gill rakers. Each filament was formed of a thin central cartilaginous core surrounded by peripheral cartilaginous matrix and covered by primary epithelial layer with abundant mucous cells. The chloride cells appeared mainly near to the base of secondary lamellae. Each gill filament gave rise to a very large number of secondary lamellae on both sides. The epithelial lining of the secondary lamellae comprised epithelial pavement cells, few mucous cells and pillar cells. The latter interposed the enriched blood capillaries. These findings suggest that L. sceleratus gills have characteristic morphological features that are related to adaptive functions for feeding habits, osmoregulation and respiratory mechanism with in their living environment.